Metformin Activation of Sirtuin 3 Signaling Regulates Mitochondrial Function Improves Diabetes-Associated Cognitive Impairment - An JF; Su H; Zhang CQ; Wang XT; Zhang GQ; Fu LY; Xu YN; Tao L; Shen XC (Diabetes, Metabolic Syndrome and Obesity, 2025)
Jiang-Fei An,1– 3,* Hang Su,1– 3,* Chun-Qiang Zhang,1– 3 Xue-Ting Wang,1– 3 Guang-Qiong Zhang,1– 3 Ling-Yun Fu,1– 3 Yi-Ni Xu,1– 3 Ling Tao,1– 3 Xiang-Chun Shen1– 3 1The State Key Laboratory of Functions and Applications of Medicinal Plants, Guizhou Medical University, Guiyang, Guizhou, 561113, People’s Republic of China; 2The High Efficacy Application of Natural Medicinal Resources Engineering Center of Guizhou Province, School of Pharmaceutical Sciences, Guizhou Medical University, Guiyang, Guizhou, 561113, People’s Republic of China; 3The Key Laboratory of Optimal Utilization of Natural Medicine Resources, School of Pharmaceutical Sciences, Guizhou Medical University, Guiyang, Guizhou, 561113, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiang-Chun Shen, Email shenxiangchun@126.comContext: Diabetes-associated cognitive impairment (DACD) is a prevalent complication of diabetes mellitus, with a strong correlation to both the severity and duration of the disease. While metformin has demonstrated a significant impact on mitigating DACD, the precise mechanisms underlying its therapeutic effects remain inadequately understood.Objective: This study aims to examine the protective effects of metformin (MET) on DACD and to elucidate the underlying mechanisms involved.Materials and Methods: C57BL/6J male mice from in vivo animal experiments established DACD by high-fat diet (HFD) for 12 weeks, combined with intraperitoneal injection of low-dose streptozotocin (STZ, 40 mg/kg). Subsequently, DACD mice were administered MET for 2 months. The expression levels of proteins related to mitochondrial function were analyzed using immunohistochemical staining, immunofluorescence double staining, qRT-PCR, and Western blot. Furthermore, the mechanism underlying the improvement of DACD by MET was validated by using the Sirtuin 3 (SIRT3) agonist resveratrol (RES), the inhibitor 3-TYP, and sh-SIRT3 on astrocytes.Results: Our findings indicate that MET significantly ameliorated mitochondrial dysfunction in DACD mice, accompanied by an upregulation of SIRT3 expression. Furthermore, comparable results were noted with the SIRT3 agonist RES. Meanwhile, suppressing SIRT3 expression via sh-SIRT3 or SIRT3 inhibitor 3-TYP in astrocytes largely abolished MET’s ability to restore mitochondrial function.Conclusion: It has been demonstrated that MET ameliorates mitochondrial dysfunction by activating the SIRT3 signaling pathway to rescue DACD.Keywords: metformin, sirtuin 3, mitochondria, diabetes-associated cognitive dysfunction, astrocytes